Hybrid Energy Storage Performance Evaluation of Fuel Cell Injection on Standalone Photovoltaic System - Indah Sulistiyowati; Jamaaluddin Jamaaluddin; Izza Anshory (Journal of Electrical Technology UMY, 2022)
In this research, some performance evaluations of battery as the main storageand supercapacitor as the supporting storage in a hybrid energy storage system werecarried out to determine the recommendations of whether fuel cells could be integratedinto a standalone photovoltaic system. In previous studies, the fuel cell circuit was judgedto be quite different by integration with a standalone photovoltaic system, and in thisstudy, observations were made on aspects of power quality such as voltage, current, andpower for the two energy storage systems. The research method is using simulation as themedium with several self-definition aspects on photovoltaic, fuel cell, battery, andsupercapacitor, also with their parameters. The result shows that on the battery, the fuelcell integration has no particular effect since the battery is the main storage, and thevoltage and current had minor perturbation. While in a supercapacitor, majorperturbation from the system had been absorbed due to the fuel cell integrationcharacteristic of giving major perturbation to the system. The main recommendation is bychoosing supporting storage instead of using both supercapacitors and fuel cells.